Teaching Patient Safety Using an Interprofessional Team-Based Learning Simulation Model in Residency Training - Wei-Hsin Lu; Nirvani Goolsarran; Carine E. Hamo; Stacey M. Frawley; Colby Rowe; Susan Lane (Association of American Medical Colleges, 2016)
Abstract Introduction Teaching and learning patient safety require demonstration of competencies such as teamwork, communication skills, and recognition of systems error. This patient safety TBL simulation-training program was developed to fulfill core patient safety objectives outlined by the ACGME and ACGME Clinical Learning Environment Review Program. The goal of the program is to enhance patient safety and quality care concepts and facilitate hands-on teamwork skills and core attitudes towards patient safety. This program served as a mandatory part of the residency core curriculum. Methods It was delivered as a 3-hour workshop session during medicine resident orientation. The workshop included an introductory presentation, one TBL activity, and three 1-hour interprofessional simulated application cases using either high-fidelity mannequins or standardized patients. Following each application case activity, trainees participated in a postcase scenario debriefing moderated by faculty facilitators. Results A total of 76 trainees participated, and 20 interprofessional teams were created. An independent-samples t test revealed that the Group Readiness Assurance Test scores were significantly higher than the Individual Readiness Assurance Test scores. Although the Readiness for Interprofessional Learning Survey's Teamwork and Professional Identity subscale scores were higher postworkshop compared to preworkshop, the differences were not statistically significant. Over 90% of the participants agreed that the safety concepts they learned would likely improve the quality of care they provide to future patients. Discussion A simulation model centered on an interprofessional team can be used as an important training technique to teach health care professionals realistic, hands-on principles of patient safety.